Evidence for topographically organized endogenous 5-HT-1A receptor-dependent feedback inhibition of the ascending serotonin system - Commons, Kathryn G. (2008)
Raphe and extra-raphe 5-HT-1A receptors contribute to feedback inhibition of serotonin (5-HT) neurons; however, the endogenous function of 5-HT-1A receptor-dependent feedback inhibition remains poorly understood. Here, the possibility that 5-HT-1A-mediated feedback inhibition of the raphe nuclei is topographically organized was examined. This was done by testing the effect of systemic blockade of 5-HT-1A receptors on Fos expression in 5-HT neurons in the dorsal raphe (DR) and median raphe (MR). The premise was that appearance of Fos after 5-HT-1A receptor blockade would implicate endogenous inhibition via 5-HT-1A-dependent processes. 5-HT-1A receptor antagonist administration (WAY-100635) in rats returned to their home cage significantly increased the number of Fos-containing 5-HT cells in the lateral wings and the ventral caudal part of the DR as compared to vehicle-injected controls, suggesting that tonic activity of brain 5-HT-1A receptors impacts on these regions. In rats receiving vehicle injections, swim, a behavior known to influence 5-HT neurotransmission, increased the number of Fos-containing 5-HT cells only in the caudal third of DR. Administration of WAY-100635 preceding a swim did not change the amount of Fos in the caudal DR, but increased the number of Fos-containing 5-HT cells in the rostral DR, lateral wings of the DR, and MR. These results confirm, using an imaging approach, that 5-HT-1A receptor-dependent feedback inhibition depends on behavioral state (return to home cage vs. swim). Moreover, they reveal that the effect of 5-HT-1A receptor blockade in each case is subregionally organized.